Clinical, ultrasound and biochemical features of polycystic ovary syndrome in adolescents: Implications for diagnosis - Hickey, M.; Doherty, D.; Atkinson, Helen; Sloboda, D.; Franks, S.; Norman, R.; Hart, R. (Oxford University Press, 2011)
BACKGROUND: Diagnosing polycystic ovary syndrome (PCOS) in adolescence is clinically challenging. The prevalence of clinical, ultrasound and biochemical features of PCOS in a community-based adolescent population using current diagnostic criteria has not previously been described. Methods This was a prospective cohort study with 244 unselected post-menarchal girls, mean age 15.2 years, of whom 91% were Caucasian. Subjects were recruited from a large population-based birth cohort (the Raine cohort). Clinical hyperandrogenism (HA) was quantified using Ferriman-Gallwey scores. In the early follicular phase (Day 2-6), we measured circulating androgens and sex hormone-binding globulin by immunoassay, and ovarian morphology was assessed by transabdominal ultrasound examination. BMI and waisthip ratio were measured. Results Normal ranges for early follicular phase androgens in adolescence were derived for this population. The top 5 and 10% of circulating free testosterone levels were 45.6 and 34.5 pmol/l, respectively. Fifty-one percent of girls reported menstrual irregularity. Clinical HA was uncommon, being observed in only 3.5% of girls. Mean ovarian volume was greater than that reported by others in adult women and 35% of girls had polycystic ovary morphology on transabdominal ultrasound. Taking the upper 5% of free testosterone as HA, 42 girls (18.5%) would have met the Rotterdam criteria for PCOS, 11 girls (5%) the Androgen Excess Society criteria and 7 girls (3.1%) the National Institutes of Health criteria. CONCLUSIONS Menstrual irregularity is common in adolescence and does not relate to clinical or biochemical HA. Diagnostic criteria for PCOS which include ovarian volume and morphology may be of limited use in adolescence. © The Author 2011. Published by Oxford Universi ty Press on behalf of the European Society of Human Reproduction and Embryology. All rights reserved.